Beyond instrument: smartphone app and sustainable mobility - Schwanen, Tim (European Journal of Transport and Infrastructure Research, 2015)
The rise of smartphones and mobile applications (apps) is of major importance to multiple recent innovations in sustainable urban mobility, including car sharing schemes and real-time information provision in public transport, as well as the recent surge in urban cycling. Yet, exactly how apps feature in these innovations and trends remains largely unclear. This paper argues that this lack of understanding reflects not only the rapid pace of developments in apps and their technical functionalities but also gaps in academics’ conceptualization of the nature of apps and their effects. Too easily and often are apps seen as mere instruments for the realisation of human-centred goals and intentions, or are their capacities and effects assumed to emerge from the webs of relations in which apps and smartphones are enmeshed. An alternative conceptualisation is therefore proposed, one that is informed principally by the object-oriented approach developed by philosopher Graham Harman. After summarising some of Harman’s original concepts and developing his account of power, the paper elaborates a series of ideas and recommendations about how the developed conceptual framework can be deployed in empirical research on the interactions between apps and physical mobility in the city.